Review of Antarctic greenhouses and plant production facilities: A historical account of food plants on the ice - Bamsey, Matthew; Zabel, Paul; Zeidler, Conrad; Gyimesi, David; Schubert, Daniel; Kohlberg, Eberhard; Mengedoht, Dirk; Rae, Joanna (2015)
Antarctic crews have been transporting plants and their supporting infrastructure to Antarctic field sites since as early as 1902. More than 46 distinct plant production facilities have, at one time or another, operated in Antarctica. Production facilities have varied significantly in size, technical sophistication, and operational life. Many of these efforts have been driven by the expeditioners themselves, which clearly demonstrates the fundamental desire that people have to associate themselves with plants while living and working in inhospitable environments. The need for this biological association can be solely psychological, while at other times it is based on the more practical need for fresh food. Although the nature of plant growth activities has evolved with the implementation of increasingly stringent environmental regulations, there remains strong interest in deploying such systems within or near Antarctic stations. Current Antarctic plant growth facilities are predominately organized and administered at the national program level to ensure such regulations are adhered to. Nine hydroponic facilities are currently operating in Antarctica. This paper summarizes historic and existing Antarctic facilities by incorporating information from expeditioners, environmental assessment reports, direct communication with national contact points, as well as published reference documents, unpublished reports, and web-based sources. A description of the country operating the facility, the specific Antarctic station, as well as specific information with regard to the facility size and the nature/type of the deployed systems are provided. Looking towards the future of Antarctic plant growth facilities, a number of previously and currently planned Antarctic facilities are also reviewed. The potential for future Antarctic plant production systems are discussed and considered not only for food production but also as bioregenerative life support systems, in that they can provide supplemental station capacity for air and ...